THE ORIGIN OF NUMBER AND THE ORIGIN OF GEOMETRY: ISSUES RAISED AND CONCEPTIONS ASSUMED BY EDMUND HUSSERL - Bicudo, Maria Aparecida Viggiani [UNESP] (Revista Pesquisa Qualitativa - RPQ, 2020)
The objective of this article is to present the concept of origin, as presented in Husserl’s initial studies, and the same concept as it appears in his final work. The views he assumed in the different phases of his life are addressed: in Halle, when he follows Brentanian psychology to support the origin of number; in Göttingen, where he remains until 1916, when his thinking about reduction matures; and the final stage in Freiburg. The article presents ways through which he understood and explained the origin of number, considered in the first phase and his first studies as central for the clarification of the fundaments of mathematics. It further presents how he explained the origin of geometry, under the dimension of the life-world, as well as his conception of knowledge and reality, already understood in the 1930s and throughout the years nearing his death as life-world.
A ORIGEM DO NÚMERO E A ORIGEM DA GEOMETRIA: QUESTÕES LEVANTADAS E CONCEPÇÕES ASSUMIDAS POR EDMUND HUSSERL
Keywords: Crisis of modern sciences; Historical a priori; Origin of geometry; Origin of number; Phenomenology